The antihyperglycemic effect of pulsed electric field-extracted polysaccharide of Kaempferia elegans officinale on streptozotocin induced diabetic mice - Lei, Huan-Qing; Li, Dong-Mei; Woo, Meng-Wai; Zeng, Xin-An; Han, Zhong; Wang, Ruo-Yong (Frontiers in Nutrition, 2022)
Kaempferia elegans polysaccharide (KEP) was extracted using a high-voltage pulsed electric field-assisted hot water method. Its physicochemical properties, in vitro activity and hypoglycemic effect was investigated. Experiments were undertaken with diabetic mice models and the potential mechanism of KEP to improve blood glucose levels was unveiled through measurements of relevant indicators in the serum and liver of the mice. Results showed that KEP is mainly composed of glucose, rhamnose, arabinose and galactose. It has certain DPPH and ABTS free radical scavenging ability and good α-glucosidase inhibitory ability, indicating that KEP has the potential to improve blood glucose levels in diabetes patients. The experimental results of KEP treatment on mice showed that KEP could control the continuous increase of fasting blood glucose levels. The potential mechanisms behind this blood glucose level control composes of (1) increasing the glucokinase and C peptide levels and decreasing Glucose-6-phosphatase content for improving key enzyme activity in the glucose metabolism pathway. This promotes the consumption of blood glucose during glycolysis, thereby inhibiting the production of endogenous glucose in gluconeogenesis pathway; (2) reducing triglyceride, total cholesterol, low density lipoprotein cholesterol and increasing high density lipoprotein cholesterol content, for regulating blood lipid indicators to normal levels; and (3) by improving the activities of catalase, glutathione peroxidase and antioxidant enzymes superoxide dismutase for further improving the antioxidant defense system in the body to reduce blood glucose.